CASTABILITY OF STEERING KNUCKLE FROM ALUMINIUM ALLOY BY LOW PRESSURE DIE CASTING REPLACING SAND CASTING OF CAST IRON - Aydin, Ramazan; Akdogan, Anil; Vanli, Ali Serdar; Durakbasa, Numan M. (TECHNICAL UNIV CLUJ-NAPOCA, FAC MACHINE BUILDING DEPT SYSTEMS ENG, 2021)
In this paper the manufacturability and useability of the steering knuckle which located at the front suspension system of mid commercial vehicles was investigated whether could be substituted from aluminium alloy by low pressure die casting method instead of conventional cast iron material with sand casting. In the detailed benchmark study, it has been observed that knuckles used in commercial vehicles generally made of cast iron material. Since lighter parts can be obtained with aluminum knuckle design it has been aimed to increase the load carrying capacity and also to achieve better fuel consumption. In addition, it is also intended to have better driving dynamics by reducing the unsprung mass and increasing the range for the electric vehicles. Primarily, both cast iron and aluminum knuckles were designed by following the related design rules. Subsequently, filling and solidification casting simulations were carried out to verify the relevant casting methods. In conclusion, strength and fatigue analyzes were carried out with the help of finite element methods to verify the structural suitability of the designs that have been made under similar vehicle loads before the prototype tooling phase.
Keywords: Steering knuckle; aluminium alloy; weight reduction; cast iron; sand casting; low pressure die casting; Mechanics